Muscle metaboreflex-induced coronary vasoconstriction functionally limits increases in ventricular contractility - Coutsos, Matthew (American Physiological Society, 2010)
Muscle metaboreflex activation during dynamic exercise induces a substantial increase in cardiac work and oxygen demand via a significant increase in heart rate, ventricular contractility, and afterload. This increase in cardiac work should cause coronary metabolic vasodilation. However, little if any coronary vasodilation is observed due to concomitant sympathetically induced coronary vasoconstriction. The purpose of the present study is to determine whether the restraint of coronary vasodilation functionally limits increases in left ventricular contractility. Using chronically instrumented, conscious dogs (n = 9), we measured mean arterial pressure, cardiac output, and circumflex blood flow and calculated coronary vascular conductance, maximal derivative of ventricular pressure (dp/dt(max)), and preload recruitable stroke work (PRSW) at rest and during mild exercise (2 mph) before and during activation of the muscle metaboreflex. Experiments were repeated after systemic α(1)-adrenergic blockade (∼50 μg/kg prazosin). During prazosin administration, we observed significantly greater increases in coronary vascular conductance (0.64 ± 0.06 vs. 0.46 ± 0.03 ml·min(−1)·mmHg(−1); P < 0.05), circumflex blood flow (77.9 ± 6.6 vs. 63.0 ± 4.5 ml/min; P < 0.05), cardiac output (7.38 ± 0.52 vs. 6.02 ± 0.42 l/min; P < 0.05), dP/dt(max) (5,449 ± 339 vs. 3,888 ± 243 mmHg/s; P < 0.05), and PRSW (160.1 ± 10.3 vs. 183.8 ± 9.2 erg·10(3)/ml; P < 0.05) with metaboreflex activation vs. those seen in control experiments. We conclude that the sympathetic restraint of coronary vasodilation functionally limits further reflex increases in left ventricular contractility.